Analisis Penerapan Teori Belajar Kognitif dalam Meningkatkan Minat Belajar IPA Siswa Kelas 6 SD - Eliyanti, Ni Kadek; Suarni, Ni Ketut; Margunayasa, I Gede (Universitas Batanghari Jambi, 2025)
This research attempts to overcome the obstacle of low learning interest in grade 6 students at SD Negeri 4 Saba in learning science by applying cognitive theory in the learning process. Experimental research with a Nonequivalent Pretest Posttest Control Group Design was conducted on 6th grade elementary school students who were divided into experimental groups and control groups using the Cluster Random Sampling Technique. Data collection was carried out through tests of science students' comprehension abilities and analyzed using the T-Polled Variance test to ensure homogeneity of data variance. The research results showed significant differences in students' interest and abilities in learning science between the group that applied cognitive development theory and the control group. Thus, the application of this theory proves a significant influence on science learning in elementary schools.